Techno-Enviro-Economic Analysis of Precipitated Calcium Carbonate Production from Carbon Dioxide in Cement Industry Flue Gas and Calcium Hydroxide - Panggabean, Natalia Debora; Purwanto, Widodo Wahyu (Journal of Materials Exploration and Findings, 2026)
CCUS is a technological solution to reduce emissions from the cement industry, which is the second largest CO2-intensive industry. This study aims to analyze technical, economic, and environmental performance of Precipitated Calcium Carbonate (PCC) synthesis in cement industry flue gas. The process simulation includes the CO2 capture system from cement plant, CO2 captured used as feedstock for PCC synthesis process through its reaction with calcium hydroxide. The simulation was carried out using ASPEN Plus software. Technical analysis was performed to determine the CO2 capture efficiency and PCC synthesis efficiency. Economic analysis was conducted to calculate CO2 capture cost and production cost of PCC based on Levelized Cost of Chemical (LCOC)). Environmental analysis was carried out with gate- to-gate scope to quantify the amount of CO2 converted per unit of PCC produced and to assess the CO2 abatement potential. The study shows that a cement plant with a production capacity of 3,000 tons of clinker per day can capture 4,542 kg/h of CO2 with a purity of 98.3% and a capture efficiency of 99.5%. Estimated CO2 capture cost was USD 65 per ton of CO2. PCC produced amounted to 8,196 kg/h with a carbonation efficiency of 80.01%, and the LCOC was USD 254 per ton of CaCO3. Overall, the process was able to reduce emissions by 0.435 tons of CO2 per ton of CaCO3 produced, with a CO2 avoidance cost of USD 92.85 per ton of CO2.